Assessment organic production of kyuri farms focuses on microbiological contamination with good agricultural practices (GAP) standard criteria. - Okta Pringga Pakpahan, Kenji Hosono Hiroyuki Nakaki (Universitas Muhammadiyah Malang, 2019)
The assessment was based on interviews result and experiment laboratory assay with the three organic kyuri farmers in Saga City focus prevention activities of microbiological contamination. Each farm the 21 samples (soil, kyuri seedlings, natural fertilizer, and water resource) were taken during six times visited or one cultivation production cycle. The object was a focus on hygiene attribute (coliforms) and safety (Salmonella spp and E. coli O157: H7), the evaluation activities of farmers' food safety practice used GAP standard as an indicator. The laboratory results in both of three kyuri farmers, coliforms ranging from 3.0 to 4.7 log 10 cfu/g, E.coli O157: H7 was detected only at the farm 3 and Salmonella spp was not detected. The evaluating activities through self-assessment tool describe all three farms have two major hazards focus, one is chemical control such as synthetic substances uses, pesticide residue and chemical contaminations, two is a microbial hazard due to contact with raw material, and natural characteristics. The overall study, the farmers in the middle level of application food safety practice.